Наближення класів BΩp,θ в функцій багатьох змінних цілими функціями у просторі Lq(Rd) - Янченко, С.Я. (Український математичний журнал, 2010)
Получены точные по порядку оценки наилучших приближений классов BΩp,θ функций многих переменных целыми функциями экспоненциального типа в пространстве Lq(Rd). Exact-order estimates are obtained for the best approximations of the classes BΩp,θ of functions of many variables by entire functions of the exponential type in the space Lq(Rd).